2016
DOI: 10.5210/fm.v21i9.6429
|View full text |Cite
|
Sign up to set email alerts
|

Led it on Reddit: An exploratory study examining opinion leadership on Reddit

Abstract: Is it possible to identify opinion leaders in a semi-anonymous online network? To answer this question, this study examines the social news site Reddit to determine whether opinion leadership can be recognized in an online network that, at face value, does not allow users to associate with their off-line personas. Identifiable characteristics, such as commenting, longevity, karma scores, posting frequency, and posting scores were analyzed. Results indicate that semi-anonymous opinion leadership may exist, as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…Our results regarding Karma scores also differ from conclusions drawn by Kilgo et al (2016), who suggested that Karma scores may be used to identify opinion leaders (i.e. highly connected individuals).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results regarding Karma scores also differ from conclusions drawn by Kilgo et al (2016), who suggested that Karma scores may be used to identify opinion leaders (i.e. highly connected individuals).…”
Section: Discussioncontrasting
confidence: 99%
“…There are no functions for users to share or like others' content, and besides the date of registration and the number of published posts, there are no metrics that, for instance, signal user's "karma," like on Reddit (cf. Kilgo et al, 2016). There are also vast possibilities for user anonymity; forum regulations even state that it is forbidden to disclose other users' identities (Flashback, 2020).…”
Section: Case Studymentioning
confidence: 99%
“…Sophisticated work has been conducted by computer scientists on automatic the process of crediblization or vetting of content. Research on Amazon reviews (e.g., Liang, 2016;Walther, Liang, Ganster, Wohn, & Emington, 2012), on Slashdot (e.g., Gosain, 2003;Stevenson, 2016) and Reddit (e.g., Kilgo et al, 2016;Lim, Carman, & Wong, 2017;Park, Conway, & Chen, 2018), as well as on social media likes, shares, and comments (e.g., Alhabash, Almutairi, Lou, & Kim, 2018;Liang & Kee, 2018), have opened the road to a very productive line of research. The core research agenda item is discovering methods to identify and mitigate or eliminate false or malevolent content or evaluations.…”
Section: Trust Credibility and Transparencymentioning
confidence: 99%